THE EFFECT OF AEROBIC EXERCISE LOW IMPACT AGAINST FUNCTIONAL MOVEMENT IN THE ELDERLY AT POSYANDU LANSIA NGUNDI RAHARJO BOYOLALI - FUTURANI, ASSA FAMILIA; SETIAWAN, CAHYO; WIDARTI, RINI; ROMADHONI, DEA LINIA (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Aerobic Low Impact  is a geriatric exercise that takes place without planning and only uses balance exercises that concentrate on certain large muscle groups with light to moderate movement intensity. Benefits This exercise in the elderly will increase the strength of the respiratory muscle pump and muscle strength, which will maintain the skeletal structure of the body. Decreased musculoskeletal function is a common problem that occurs in the elderly, one of which is characterized by decreased joint flexibility. Decreased joint firmness in the elderly reaches 40-50%. Strong muscles and good flexibility are protective for the elderly. Purpose: To find out whether there is an effect of Low Impact Aerobic Exercise on Functional Movement in the elderly.  Methods: this type of research is a quantitative research, quasy-experimental (Quasy Experimental) with One Group PreTest PostTest Design with a sample size of 23. The research instruments used questionnaires, interviews and functional movement measurements using FMS (Functional Movement Screening). The Low Impact Aerobic Exercise Intervention was carried out 2 times a week for 2 weeks with a duration of 25-30 minutes of exercise. Result: the results of the study obtained a significance value of FMS of 0.157 (p0.05). then Ho is accepted Ha is rejected so that it can be interpreted that there is no effect of Aerobic Low Impact  Gymnastics on Functional Movement in the elderly. Conclusion: There is no effect of Low Impact Aerobic Exercise on Functional Movement in the elderly.)